Aspiration thrombectomy versus stent retriever thrombectomy alone for acute ischemic stroke: evaluating the overlapping meta-analyses. (18th May 2022) - Azzam, Ahmed Y; Ghozy, Sherief; Kallmes, Kevin M; Adusumilli, Gautam; Heit, Jeremy J; Hassan, Ameer E; Kadirvel, Ramanathan; Kallmes, David F
Abstract : Background: Previous studies comparing a direct aspiration first pass technique (ADAPT) and stent retrievers have inconsistent methodologies and data reporting, limiting the ability to accurately assimilate data from different studies that would inform treatment of acute ischemic stroke (AIS) treatment. Objective: To conduct a systematic review to discuss and compare the findings of all relevant meta-analysis studies comparing the efficacy of the ADAPT and stent retriever techniques. Methods: The study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), where meta-analyses comparing the efficacy of the ADAPT technique and stent retrievers in the treatment of AIS were included. We extracted all relevant data from the included studies and assessed the quality of the included meta-analyses using the Assessment of Multiple Systematic Review (AMSTAR-2). Results: Seven relevant studies met our inclusion criteria and were suitable for the qualitative synthesis. All included studies obtained data from randomized controlled trials (RCTs) and observational investigations (including levels II, III, and IV). At the same time, none of them used the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) for quality assessment. In accordance with AMSTAR-2, two studies were rated 'high', while the other five were rated 'moderate'. Conclusions: Present evidence is insufficient to clarify the superiority of one modality over the other. Further RCTs on this comparison must be conducted prior to designing further meta-analyses or making conclusive interpretations. Procedure duration and cost should be taken into consideration for any future studies.